Virulence factors of non-Candida albicans Candida species - Silva, Sónia Carina (2010)
Candidosis caused by non-Candida albicans Candida (NCAC) species have been increased in recent years, namely due Candida glabrata, Candida tropicalis and Candida parapsilosis. Furthermore, candidosis is facilitated by a number of virulence factors, such as adherence to medical devices and/or host cells, biofilm formation and secretion of enzymes. Thus, the main goal of this study was to characterize clinical isolates of C. glabrata, C. tropicalis and C. parapsilosis recovered from different body sites (oral cavity and urinary and vaginal tracts).in terms of the most important virulence factors (adhesion, biofilm formation ability, tissue colonization and invasion, and expression of secreted aspartly proteinases).